Evaluation of Tuberculosis Treatment Response With Serial C-Reactive Protein Measurements. (10th October 2018) - Wilson, Douglas; Moosa, Mahomed-Yunus S; Cohen, Ted; Cudahy, Patrick; Aldous, Collen; Maartens, Gary
Abstract: Background: Novel biomarkers are needed to assess response to antituberculosis therapy in smear-negative patients. Methods: To evaluate the utility of C-reactive protein (CRP) in monitoring response to antituberculosis therapy, we conducted a post hoc analysis on a cohort of adults with symptoms of tuberculosis and negative sputum smears in a high–tuberculosis and HIV prevalence setting in KwaZulu-Natal, South Africa. Serial changes in CRP, weight, and hemoglobin were evaluated over 8 weeks. Results: Four hundred twenty-one participants being evaluated for smear-negative tuberculosis were enrolled, and 33 were excluded. Two hundred ninety-five were treated for tuberculosis (137 confirmed, 158 possible), and 93 did not have tuberculosis. One hundred and eighty-three of 213 (86%) participants who agreed to HIV testing were HIV positive. At week 8, the on-treatment median CRP reduction in the tuberculosis group (interquartile range [IQR]) was 79.5% (25.4% to 91.7%), the median weight gain was 2.3% (−1.0% to 5.6%), and the median hemoglobin increase was 7.0% (0.8% to 18.9%); P < .0001 for baseline to week 8 comparison of absolute median values. Only CRP changed significantly at week 2 (median reduction [IQR], 75.1% [46.9% to 89.2%]) in the group with confirmed tuberculosis and in the possible tuberculosis group (median reduction [IQR], 49.0% [−0.4% to 80.9%]). Failure of CRP to reduce to ≤55% of the baseline value at week 2 predicted hospitalization or death in both tuberculosis groups, with 99% negative predictive value. Conclusions: Change in CRP may have utility in early evaluation of response to antituberculosis treatment and to identify those at increased risk of adverse outcomes.